Linear and Nonlinear Heart Rate Variability Analysis in Gonadal Dysgenesis (Swyer Syndrome): A Case Report - Pereira, Valdelias Xavier; Carvalho, Tatiana Dias De; Marinovic, Marcos Antonio; Norberto, Alex Rey; Soares, José Maria; Valenti, Vitor Engrácia [UNESP]; Sorpreso, Isabel Cristina Esposito (Sociedade Brasileira de Cardiologia, 2021)
Swyer syndrome is one of the disorders of sexual differentiation. Previous studies have demonstrated increased sympathetic activity with heart rate variability (HRV) analysis with decreasing estradiol levels. One patient presented a pure 46, XY gonadal dysgenesis with female phenotype. Cardiac autonomic modulation was assessed through HRV analysis while at rest. This research analyzed linear and nonlinear indexes. HRV analysis showed reduced parasympathetic and global modulation with an apparent increase in sympathetic tone and a loss of HR fractal dynamics toward correlated behavior, characterized by low entropy and high determinism of time series.
Keywords: Autonomic Nervous System; Estrogen; Replacement Therapy; Amenorrhea; Gonadectomy; Heart Rate; Cardiovascular Diseases/complications